Estimating the economic costs of Indigenous health inequities in New Zealand: a retrospective cohort analysis. Issue 10 (20th October 2022) - Reid, Papaarangi; Paine, Sarah-Jane; Te Ao, Braden; Willing, Esther J; Wyeth, Emma; Vaithianathan, Rhema; Loring, Belinda
Abstract : Objectives: Despite significant international interest in the economic impacts of health inequities, few studies have quantified the costs associated with unfair and preventable ethnic/racial health inequities. This Indigenous-led study is the first to investigate health inequities between Māori and non-Māori adults in New Zealand (NZ) and estimate the economic costs associated with these differences. Design: Retrospective cohort analysis. Quantitative epidemiological methods and 'cost-of-illness' (COI) methodology were employed, within a Kaupapa Māori theoretical framework. Setting: Data for 2003–2014 were obtained from national data collections held by NZ government agencies, including hospitalisations, mortality, outpatient and primary care consultations, laboratory and pharmaceutical usage and accident claims. Participants: All adults in NZ aged 15 years and above who had engagement with the health system between 2003 and 2014 (deidentified). Primary and secondary outcome measures: Rates of 'potentially avoidable' hospitalisations and mortality as well as 'excess or underutilisation' of healthcare were calculated, as the difference between actual rates for Māori and the rate expected if Māori had the same rates as non-Māori. These differences were then quantified using COI methodology to estimate the financial cost of ethnic inequities. Results: In this conservative estimate, health inequities between Māori and non-Māori adults cost NZ$863.3 million per year. Direct costs of NZ$39.9 million per year included costs from ambulatory sensitive hospitalisations and outpatient care, with cost savings from underutilisation of primary care. Indirect costs of NZ$823.4 million per year came from years of life lost and lost wages. Conclusions: Indigenous adult health inequities in NZ create significant direct and indirect costs. The 'cost of doing nothing' is predominantly borne by Indigenous communities and society. The net cost of adult health inequities to the government conceals substantial savings to the government from underutilisation of primary care and accident/injury care.